2013
DOI: 10.1158/1535-7163.mct-12-0862
|View full text |Cite
|
Sign up to set email alerts
|

Dual PI3K/AKT/mTOR Inhibitor BEZ235 Synergistically Enhances the Activity of JAK2 Inhibitor against Cultured and Primary Human Myeloproliferative Neoplasm Cells

Abstract: Hemopoietic progenitor cells

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 54 publications
5
63
1
1
Order By: Relevance
“…Banked, delinked, and deidentified, normal or AML CD34 þ or AML CD34 þ CD38-LIN À bone marrow progenitor/stem cells were purified, as previously described (18). The clinical presentation of the patient and mutation status of the primary AML samples used in these studies is provided in Supplementary Table S1.…”
Section: Primary Normal Progenitor and Aml Bpcsmentioning
confidence: 99%
See 2 more Smart Citations
“…Banked, delinked, and deidentified, normal or AML CD34 þ or AML CD34 þ CD38-LIN À bone marrow progenitor/stem cells were purified, as previously described (18). The clinical presentation of the patient and mutation status of the primary AML samples used in these studies is provided in Supplementary Table S1.…”
Section: Primary Normal Progenitor and Aml Bpcsmentioning
confidence: 99%
“…In previous reports, we demonstrated that treatment with hydroxamic acid analog pan-histone deacetylase (HDAC) inhibitors, such as panobinostat (LBH589), induces hyperacetylation of histones as well as mediates growth arrest and apoptosis of cultured and primary AML cells (17,18). Concomitantly, panobinostat treatment attenuated the levels of progrowth and prosurvival proteins, for example, BCL2 and c-MYC, while simultaneously inducing the levels of proapoptotic protein BIM (17)(18)(19).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Combining different therapies against multiple ‘oncogene addictions’ could be a possibility to overcome primary or acquired resistance. Targeted approaches in solid cancers inhibit common downstream mediators of known oncogenes, such as MEK-ERK or the PI3K-AKT-mTOR kinase pathways, and similar pathways may also play a role in oncogenesis in hematopoietic malignancies [13]. Last, newer therapeutic strategies aim to exploit the specific dependency of cancer cells on basic cellular processes such as cell division, chromatin regulation, and metabolism.…”
Section: Identification Of Key Driver Mutations In Hematopoietic Cancermentioning
confidence: 99%
“…It was shown through genetic experiments that particularly the activation of the two STAT5 transcription factors is crucial for PV [20]. Hyperactive JAK2 promotes prominent activation of the PI3K-AKT-mTOR and the RAS-RAF/MAPK-ERK pathways, among other less prominent signaling pathways, and evades negative-regulation by SOCS proteins [13]. …”
Section: Targets In Mpn and Driver Mutationsmentioning
confidence: 99%